Energy planning using multicriteria decision analysis and goal programming based on key decision makers' objectives the case of Palawan - Rodriguez, Genev Yesiree M.; Tamayao, Mili-Ann M. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Energy planning is usually done with the objective to produce electricity with the least cost while meeting the energy demand of the consumers. However, there is now an emphasis on environmental concerns, and some of the energy technologies can have trade-offs or effects on the environment. Electricity cost and environmental impacts cover only two of the three pillars of sustainability - economic, environmental, and social. Other important objectives include minimizing greenhouse gas emission, total air pollution, direct land and water use, maximizing social acceptability, job creation, capacity factors, efficiency, and responsiveness to demand. Solution alternatives are usually identified based on available generation technologies, available resources, and demand. This study developed a method that explicitly incorporates identification! and integration of decision-maker objectives to the usual energy planning approach using Value Focused Thinking (VFT), Multi-criteria Decision Making (MCDA), and Goal Programming. VFT is used to extract the objectives of the decision makers by determining their fundamental and means objectives. VFT approach is based on objective-based solutions, enabling consideration of alternatives beyond those at hand. VFT helps prevent solutions that propagate bias due to familiarity or preconceived benefits of an energy technology. MCDA is used as a framework to translate objectives to attributes and metrics as well as identify the preferences of the decision makers. Goal Programming is used with MCDA to mathematically identify the optimal energy mix given the decision makers' objectives and preferences, the resource constraints, available technologies and their respective performance as well as the energy demand. The proposed method consists of eight steps: (1) identify the decision-makers for energy planning; (2) define the energy problem or decision context; (3) determine the objectives and distinguish fundamental and specific objectives; (4) determine the attributes; (5) determine the alternatives (in the research, these are the energy technologies to be considered); (6) determine the weights of the decision-maker; (7) formulate and implement the goal programming model; and (8) perform sensitivity analysis. The method was applied to the Province of Palawan. The current local energy plan was determined using least cost method resulting in an energy mix of 70% hydropower run of river, 17% biomass, 11% piston engine and 2% solar photovoltaic. This is compared to the proposed method where the derived optimal energy mix was -69% hydropower run of river, -1% hydro dam type and -30% natural gas. The expected utility calculation of the two mixes indicates that the proposed method can yield an energy mix with higher utility - 4.491 and 4.178 for proposed method and current plan, respectively.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Energy policy -- Mathematical models; Energy policy -- Philippines -- Palawan Island